2016
DOI: 10.1097/sap.0000000000000361
|View full text |Cite
|
Sign up to set email alerts
|

In Vitro Characteristics of Porcine Tendon Hydrogel for Tendon Regeneration

Abstract: After reconstitution and digestion, porcine hydrogel was capable of supporting growth of human ASCs. The minimal difference in proliferative capacity suggests that porcine tendon hydrogel may be an effective and viable alternative to human hydrogel for the enhancement of tendon healing.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 50 publications
0
7
0
Order By: Relevance
“…While there were promising initial ex vivo functional studies with human tendon sources, others looked to transition to more commercially sustainable sources, including porcine [83] and equine [41]. Crowe et al .…”
Section: Musculoskeletal Tissuesmentioning
confidence: 99%
See 3 more Smart Citations
“…While there were promising initial ex vivo functional studies with human tendon sources, others looked to transition to more commercially sustainable sources, including porcine [83] and equine [41]. Crowe et al .…”
Section: Musculoskeletal Tissuesmentioning
confidence: 99%
“…Source species can be xenogeneic, typically from porcine or bovine sources, allogeneic from cadaveric donor tissue sources, or autologous in rare cases. A few studies directly compared porcine and human sources [68, 74, 83]. It was shown that human myocardial sources had decreased mechanical stiffness compared to porcine [68].…”
Section: Translational Considerationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, moral and religious objections could be raised to the use of (decellularized) human tissues, especially cadaveric tissues, as scaffold components. Synthetic scaffolds, 97 animal-derived scaffolds, 72 , 98 or (decellularized) tissues from living donors 99 , 100 would therefore be preferred.…”
Section: Resultsmentioning
confidence: 99%